2018
DOI: 10.1137/16m1107735
|View full text |Cite
|
Sign up to set email alerts
|

A Max-Plus Approach to Incomplete Cholesky Factorization Preconditioners

Abstract: Abstract. We present a new method for constructing incomplete Cholesky factorization preconditioners for use in solving large sparse symmetric positive-definite linear systems. This method uses max-plus algebra to predict the positions of the largest entries in the Cholesky factor and then uses these positions as the sparsity pattern for the preconditioner. Our method builds on the max-plus incomplete LU factorization preconditioner recently proposed in [J. Hook and F. Tisseur, SIAM J. Matrix Anal. Appl., 38 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Finally, we observe that there is a lack of iterative methods and preconditioners that can be used to extend the size of LSE problems that can be solved. We have shown that using an incomplete factorization within a block factorization of an augmented system can be effective, but most current incomplete factorizations that result in efficient preconditioners are serial in nature and not able to tackle extremely large problems (but see [1,25] for novel approaches that are designed to exploit parallelism). Addressing the lack of iterative approaches is a challenging subject for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we observe that there is a lack of iterative methods and preconditioners that can be used to extend the size of LSE problems that can be solved. We have shown that using an incomplete factorization within a block factorization of an augmented system can be effective, but most current incomplete factorizations that result in efficient preconditioners are serial in nature and not able to tackle extremely large problems (but see [1,25] for novel approaches that are designed to exploit parallelism). Addressing the lack of iterative approaches is a challenging subject for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we observe that there is a lack of iterative methods and preconditioners that can be used to extend the size of LSE problems that can be solved. We have shown that using an incomplete factorization within a block factorization of an augmented system can be effective but most current incomplete factorizations that result in efficient preconditioners are serial in nature and not able to tackle extremely large problems (but see [20] for a novel approach that is straightforward to parallelise). Addressing the lack of iterative approaches is a challenging subject for future work.…”
Section: Discussionmentioning
confidence: 99%
“…We observe that the counts are relatively insensitive to p but, as p increases, it The first is the Matlab variant ichol with the global diagonal shift set to 0.1 and default values for other parameters and the second is the Matlab interface to the incomplete Cholesky (IC) factorization preconditioner HSL_MI28 [39] from the HSL library [20] using the default parameter settings. IC preconditioners are widely used but their construction is often serial, potentially limiting their suitability for very large problems (see [19] for an IC preconditioner that can be parallelised). In terms of iteration counts, the Nyström-Schur and the HSL_MI28 preconditioners are clearly superior to the simple ichol preconditioner, with neither consistently offering the best performance.…”
Section: 3mentioning
confidence: 99%